Uruguay round of multilateral trade negotiations : Commonwealth interests and opportunities (Commonwealth Secretariat LondonGB, 1986)
Examines need for holding another Round and the environment in which negotiations will occur. Explores particular concerns and interests of developing countries in the Round such as the treatment of agricultural trade and improvements in a number of main articles of the GATT. Examines key issues emerging in the preparatory work of Contracting Parties. These include inter alia, dispute settlement, tropical and natural resource products, and counterfeit goods. Discusses a phased approach to GATT negotiations noting objectives and content of 3 phases. Explores prospects for progress on each of the major issues within the framework of a broad strategy for achieving progress which reflects interests of all participants.
IDS